A new species of the fishfly genus Ctenochauliodes van der Weele (Megaloptera: Corydalidae) from Vietnam. (3rd April 2022) - Liu, Xingyue; Hayashi, Fumio; Letardi, Agostino
ABSTRACT: Ctenochauliodes van der Weele is an oriental endemic fishfly genus (Megaloptera: Corydalidae: Chauliodinae), currently with 13 species. Here, we report a new species of Ctenochauliodes, namely Ctenochauliodes denticulatus sp. nov., from central Vietnam. The new species is featured by the specialised male gonocoxites 11, which bear a pair of robust, clavate gonostyli 11. An updated key to the species of Ctenochauliodes is also given.